Defective bile salt biosynthesis and hydroxylation in mice with reduced cytochrome P450 activity12. Issue 4 (18th January 2013) - Kunne, Cindy; Acco, Alexandra; Hohenester, Simon; Duijst, Suzanne; de Waart, Dirk R.; Zamanbin, Alaleh; Oude Elferink, Ronald P.J.
Abstract The difference in bile salt (BS) composition between rodents and humans is mainly caused by formation of muricholate in rodents as well as by efficient rehydroxylation of deoxycholic acid. The aim of this study was to characterize bile formation in a mouse model (Hrn mice) with hepatic disruption of the cytochrome p450 (CYP) oxidoreductase gene, encoding the single electron donor for all CYPs. Bile formation was studied after acute BS infusion or after feeding a BS‐supplemented diet for 3 weeks. Fecal BS excretion in Hrn mice was severely reduced to 7.6% ± 1.8% of wild‐type (WT), confirming strong reduction of (CYP‐mediated) BS synthesis. Hrn bile contained 48% ± 18% dihydroxy BS, whereas WT bile contained only 5% ± 1% dihydroxy BS. Upon tauroursodeoxycholate infusion, biliary BS output was equal in WT versus Hrn, indicating that canalicular secretion capacity was normal. In contrast, taurodeoxycholic acid (TDC) infusion led to markedly impaired bile flow and BS output, suggesting onset of cholestasis. Feeding a cholate‐supplemented diet (0.1%) resulted in a completely restored bile salt pool in Hrn mice, with 50% ± 9% TDC and 42% ± 10% taurocholic acid in bile, as opposed to 2% ± 1% and 80% ± 3% in WT mice, respectively. Under these conditions, biliary cholesterol secretion was strongly increased in Hrn mice, whereas serum alanine aminotransferase levels were decreased. Conclusion: Hrn mice have strongly impaired bile salt synthesis and (re)hydroxylation capacity and are more susceptible to acute TDC‐induced cholestasis. In this mouse model, a more‐human BS pool can be instilled by BS feeding, without hepatic damage, which makes Hrn mice an attractive model to study the effects of human BS. (HEPATOLOGY 2013)